PERAN SATGAS COVID 19 DALAM UPAYA PENINGKATAN PENGETAHUAN, PENCEGAHAN DAN PENGENDALIAN PENYEBARAN COVID 19: THE ROLE OF THE COVID-19 TASK IN EFFORTS TO INCREASE KNOWLEDGE, PREVENT AND CONTROL THE SPREAD OF COVID 19 - Ainnur Rahmanti; Intan Alawiyah; Eka Wahyu Amelia (JURNAL KEPERAWATAN SISTHANA, 2021)
The impact of Covid 19 occurs in all aspects of life, even 80% of the impact occurs in the non-health sector. Therefore, the management of Covid 19 needs to involve all elements of society, including the campus community. The campus community is expected to actively take social action and be at the forefront of carrying out social change, including responding to disasters. Higher education is responsible for teaching awareness of various social problems to its campus community. Efforts made by the campus in carrying out prevention started from policy development, development of supporting instruments for the Covid 19 alert campus, mobilizing Covid 19 volunteers to the formation of the Covid task force team.